ANALISIS NILAI TAMBAH KUE PIA PADA INDUSTRI RUMAH TANGGA KARYA âAN-NURâ DI KOTA PALU - Ahyadi, Ahyadi; Lamusa, Arifuddin (AGROTEKBIS, 2016)
This study aims to determine the added value derived from green beans when processed into cakes pia on Industry Household karya "AN-NUR" in Palu. The location determination is done intentionally (purposive) with the consideration that the Industry of Household Karya "AN-NUR" is central to the production of cakes pia. Respondents in this study is the leadership and employees of Industry of Household Work "AN-NUR" in BTN Palupi Block I1 No. 12 District of South Palu Palu. Respondent committed intentionally by the consideration that the leadership and employees can provide information about the processing of green beans into pia pastry and data required. The number of respondents as many as 4 people, consisting of 1 and 3 industry leaders Household Industrial employees Karya "AN-NUR". Collecting data on the analysis of the added value of this research consists of two types of data namely primary and secondary data. The analysis is the analysis of the value added by Hayami method. The results showed that the value added is the difference between the value of output, the contribution of other inputs and raw material prices. Industrial added value of Household Karya "AN-NUR" is equal Rp76.091,67/ (Kg). The ratio of the value added is a percentage of the value added to the value of output, the magnitude of the ratio of value added to the Domestic Industry Karya "AN-NUR", ie by 72%, resulting from the ratio of value added to the value of the product by 72%, indicating that every Rp 100 value pia pastry products will be obtained added value of Rp 72. Key Words: Added value, Cake Pia, industry household